TWO-DIMENSIONAL MATHEMATICAL MODEL FOR MONITORING AND FORECASTING THE PROCESS OF IN-SITU LEACHING IN A POROUS MEDIUM - Ravshanov , N; Usmonov , L (Scientific practical conference, 2025)
This research paper investigates the hydrodynamic processes of in-situ leaching, with a focus on the acid-based extraction of valuable metals from ore deposits. A mathematical model, grounded in filtration-convection and diffusion principles relevant to underground leaching, has been formulated to facilitate a thorough understanding, monitoring, and prediction of system dynamics. The model accounts for the influence of hydrodynamic parameters, including the filtration coefficient and medium porosity, which are contingent on pressure conditions and process kinetics. The overarching goal of this study is to safeguard groundwater resources from potential contamination.